Buildings and Structures as the Object of Real Property Taxes in the Countries of the Visegrad Group - Vartašová, Anna (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
In this paper, the author compares the legal regulation of real property taxes applied in the Visegrad countries (Slovakia, Czechia, Hungary and Poland) in terms of the means of determination of part of its object, namely the buildings and structures. Based on the analysis of these national regulations, the author concludes that, despite all the analysed states apply taxation of buildings and/or structures within their real property tax(es), there are conceptual differences among the particular states’ policy in determining the objects subject to tax. While the author concludes on the broadest range of taxable objects to be in Poland and the narrowest in Slovakia, there is a lot of room for inspiration and for legislative adjustments for the Slovak legislation.This paper was supported by grant project VEGA No. 1/0214/21.